DIGITAL MARKETING PERSPEKTIF EKONOMI ISLAM - Sriayu Aritha Panggabean (KOLONI, 2022)
The development of an increasingly modern era demands that all sides of life be carried out in a modern way as well. Nowadays access to the digital space is absolutely necessary and has been applied to almost all lines of life including marketing. This research will capture up close about digital marketing from an Islamic economic perspective. This research uses the literature method by conducting an authoritative search for books and journals. The results of this study show that digital marketing is allowed in Islam with the provision that 1) it is carried out on the basis of mutual liking (ridha), 2) so that the marketing carried out aims to establish brotherhood (silaturahmi), and 3) Islam prohibits marketing that contains elements of fraud (gharar). Keywords: Digital Marketing, Islamic Economics